Proyecto de factibilidad para la comercialización de bicicletas eléctricas para la empresa A& M Sistem´s en la provincia de Cotopaxi cantón Latacunga para el año 2019. - Cevallos Villavicencio, Cristina Johana (2020)
The constant population growth and the exorbitant increase in the automotive fleet, brings a series of problems such as congestion, traffic accidents and pollution, causing a world level to look at alternatives to solve these problems. One of the practical solutions for mobility is electric bicycles, Ecuador being one of the countries where it has begun to gain strength, highlighting cities such as Quito, which makes 296 electric bicycles available for public use through its mobility system “BiciQ”. Therefore, the need for the company A&M SYSTEM'S and the objective of developing a feasibility project for the commercialization of electric bicycles in the province of Cotopaxi by 2019, considering this province as a possible market niche as it is one of the ten with the highest number of vehicles nationwide. For the study, a qualitative and quantitative methodology is used which, through market, technical, economic, financial and environmental analysis will determine the feasibility of the project. In the field research, the survey is applied as a tool, obtaining a sample of 383 people after using the simple random method. Once the study is completed, it is concluded that the project is viable with a total investment of $ 42,933.87, a NPV of $ 18,244.70, an IRR of 39.13% and a Discount Rate of 16, 2% and an acceptance of 53% of the population universe.